Nitric oxide supply reduces ethylene production, softening and weight loss in papaya fruit - Machado,Marina Reggio (2022)
ABSTRACT Nitric oxide application has been seen as a promising technique to extend the postharvest life of various fresh fruits and vegetables. This is the first work involving the spray application of nitric oxide donor S-nitrosoglutathione (GSNO) on Golden papaya. Considering that results are very distinct depending on the type of the nitric oxide donor, the form of application, the concentration used and the species studied, the application must be adapted to each necessity. The aim of this study was to relate the application of GSNO, spray applied at 10, 100, 1,000 ?M, with the physiological, physical-chemical, and biochemical changes of Golden papaya, in the first 72 h of ripening. Control fruit was sprayed with distilled water. GSNO application did not interfere on color and chlorophyll fluorescence of the peel, on soluble solids, titratable acidity, lipid peroxidation, and in the level of S-nitrosothiols. Control fruit and 10-?M GSNO sprayed showed lower respiration. After 72 h of ripening at 25°C, all fruits showed an increase in ethylene biosynthesis, except for those treated with 10 ?M GSNO. Papaya sprayed with 10-?M GSNO showed the highest pulp firmness and 52% less weight loss when compared to control fruit. GSNO was also responsible for increasing the ascorbic acid in papayas, besides showing an increase in total antioxidant activity production. The results indicated that the application of 10 ?M of GSNO by spray can potentially preserve the quality characteristics of Golden papaya, mainly due to the lower ethylene production, the delay in the firmness loss, and the less weight loss.